Perceptions of invited seminar speakers and seminar organizers across university biology departments in virtual formats - Heim, Ashley B.; Hutto, Rachel (Frontiers in Education, 2023)
Research seminars are a staple within biology and other science, technology, engineering, and mathematics (STEM) departments across academic institutions. During the COVID-19 pandemic, academic institutions across the U.S. had to rapidly transition courses, research programs, and other events from in-person to virtual environments-and departmental research seminars were no exception. We explored the perceptions of biology department seminar speakers and organizers regarding the benefits and challenges they experienced in the virtual format. We asked three primary research questions: (1) What challenges and benefits do invited seminar speakers in biology departments perceive regarding presenting seminars in the virtual environment? (2) What challenges and benefits do organizers of biology department seminars perceive regarding organizing seminars in the virtual environment? (3) How did biology department seminars change during the transition from an in-person to virtual format? In total, 39 seminar organizers and 90 seminar speakers completed surveys focused on their perceptions of virtual seminars. Using descriptive statistics and thematic analysis, we found that numerous benefits and challenges are perceived by seminar speakers and organizers regarding virtual seminars. Speakers and organizers perceived similar benefits of virtual seminars including accessibility and diversity, while perceived challenges included the loss of professional networking opportunities and academic community. There was overwhelming consensus from speakers and organizers alike that virtual departmental seminars are professionally and academically valuable. However, while speakers' chief motivator was in furthering their own networks, research collaborations, and research visibility, organizers primarily valued their own students' or trainees' career development as well as their own departmental community. Together, these findings demonstrate the potential benefits of continuing virtual seminars outside of the context of the COVID-19 pandemic from an equity perspective while also highlighting issues that must be addressed by organizers and attendees to ensure seminars retain their value.